The effect of testing and feedback on the forgetting curves for radiograph interpretation skills. (3rd July 2019) - Boutis, Kathy; Pecaric, Martin; Carrière, Benoit; Stimec, Jennifer; Willan, Andrew; Chan, Julie; Pusic, Martin
Abstract: Objectives: Forgetting curves plot skill decay over time. After exposure to a simulation-based radiograph interpretation learning system, we determined the rate of learning decay and how this was impacted by testing (with and without feedback). Further, we examined the association of initial learning parameters on the forgetting curve. Methods: This was a multicenter, four-arm randomized control trial. Medical trainees completed 80 elbow radiographs and a 20-case post-test. Group 1 had no testing until 12 months; Groups 2–4 had testing every 2 months until 12 months. At 6 months, Group 3 testing was feedback-enhanced, while Group 4 had feedback-enhanced testing at 2, 6, and 10 months. Results: There were 106 participants ( n = 42 Group 1; n = 22 Groups 2 and 3; n = 20 Group 4). Group 1 showed an –8.1% learning decay at 12-months relative to other groups. In Groups 2, 3, and 4, there was no significant learning decay (+0.8%), and there were no differences in skill decay between these groups. Initial score and learning curve slope were predictive of retained skill. Conclusions: Learning decay was mitigated by exposure to 20 test cases (with and without feedback) every two months. Initial learning parameters predicted learning retention and may inform refresher education scheduling.